Vocabulary Analysis of Finnish University Students’ English Essays: a Lexical Sophistication and Content Analysis Study - Peltomäki, Nelli (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis studied the vocabulary development and the content of Finnish university students’ essays. The data belong to the ACALEX corpus. Word frequency was examined to see whether there was a change in the vocabulary of the students after an academic English writing course. This was done by inserting two self-assessment and one academic essay from each student to an online program called VocabProfile, which divides the words used in the essays to frequency bands. Two bands were looked at in more detail: the first thousand most frequent words in the English language and academic vocabulary. It was found that there was an increase in the use of academic vocabulary and a decrease in the use of the most frequent words. However, the results were not very striking. Moreover, the size of the sample does not permit generalization of the results. In addition, the content of the essays was examined. The students wrote about similar enough topics so that three common themes were found, which came to be the research questions for the content analysis part of the study. These were: how do the students describe their language skills; what do the students think about academic language; and how do the students learn languages the best? The content analysis included a process of qualitative coding of the self-assessment essays. It was found that the codes from the first theme concerned students’ uncertainty about their own skills and getting more confidence after the course; codes from the second theme handled students’ unfamiliarity with academic language and at the end of the course the feeling they have learnt the basics of it; codes from the third theme related mostly to implicit learning of English during their leisure time, but also to the appreciation of the tasks the course offered. The limitations of the study were its small sample size and the fact that the research design of the study differed from previous studies to the point where this study is not strictly comparable with other studies of similar topic. Moreover, statistical methods and quantitative coding might have lessened the effects of subjectivity of the analysis. However, this study concentrated more on qualitative research and forming a comprehensive picture of this particular group of students. In addition to adding statistical methods and quantitative coding to the research design, future research suggestions included comparing lexical sophistication results with more variables, for instance syntactic knowledge.